Psychosocial Status of Patients with Chronic Heart Failure Awaiting Heart Transplantation - Roman Yu. Shindrikov; Olga Yu. Shchelkova; Elena A. Demchenko; Mariya Yu. Sitnikova (Peoples' Friendship University of Russia (RUDN University), 2019)
A pilot study of psychosocial status of 80 patients (85% males) with terminal chronic heart failure (CHF), during the preparation for heart transplantation (HT) has been carried out in the Almazov National Medical Research Centre. The correlation of psychological, medical, biological and socio-demographic characteristics of patients as well as the dynamics of patients' emotional state (anxiety and depression) during a long cardiology hospital stay (4 measurements over half a year) has been studied. The authors' structured interview and a set of psychodiagnostic methods ("Index of General Well-being", "Brief neuropsychological examination of cognitive sphere", depression scale (SDS), scale of anxiety (STAI), personality questionnaire BIG-V) have been used in the study. For mathematical and statistical data processing the following methods included in the software package SPSS v. 20.0 have been used: the Pearson's chi-squared test (χ2), the Mann - Whitney U test, the Spearman and Pearson correlations, and ANOVA. The results revealed the absence of clinically significant signs of depression, cognitive impairment, personality and system of significant relationships in the majority of patients at the first stage of the study (upon admission into hospital). The exception was the increased level of situational anxiety (M ± m = 43.2 ± 7.1). The study of the dynamics of the emotional state of patients reflected a systematic increase in the average group indices of the depression scale (upon admission M ± m = 46.9 ± 6.7; after 2 months M ± m = 48.9 ± 7.4; after 4 months M ± m = 51.1 ± 7.6; after 6 months M ± m = = 52.6 ± 7.5), as well as a decrease in the level of situational anxiety at the second stage of the study compared with the first and a further increase starting from the second period: after 2, 4, 6 months of the stay in hospital, respectively: M ± m = 41.3 ± 5.2; M ± m = 46.7 ± 6.8; M ± m = 50.8 ± 7.9). It was revealed that the level of situational anxiety at the second (F = 6.18; p < 0.05) and the third (F = 4.11; p < 0.05) stages of treatment is significantly higher in the patients after myocardial infarction(s). Also, the level of situational anxiety is higher at the first (F = 4.00; p < 0.05) and third (F = 3.68; p < 0.05) stages of hospitalization of the patients who have rare meetings with relatives as compared to the patients who are often visited by their relatives. The results reflect the psychosocial potential of patients waiting for HT, and may have a prognostic significance in relation to adherence to treatment in the postoperative period, which, in turn, largely determines the survival of patients.